Prognosis Supercomputer Modelling of Welded Structures Behaviour under Dynamic Loads. (2016) - Klimau, Kirill; Medvedev, Sergey
Abstract: Principles of constructive and technological design, advanced supercomputer modeling of welded structures under dynamic loads were developed. The results of the experimental computational verification of the proposed approaches are presented. New themes of investigation and production work are pointed out.